Edge detection of MRI images using artificial neural network - Gunawan, Teddy Surya; Kartiwi, Mira; Abdul Malik, Noreha (Malaysian Medical Association, 2017)
Introduction Many methods have been proposed for MRI tissue segmentation. It has been identified that MRI image of human tissue is homogeneous and the structure of each is tissue connected, but it is rather difficult to separate the adjacent tissue due to the small intensity changes or smooth boundaries observed. Current traditional edge detection performance could be further improved using artificial neural network (ANN) based edge segmentation.